A review of the United Arab Emirates healthcare systems on medical tourism and accreditation - Alshamsi, Amna I. (Frontiers in Health Services, 2024)
This paper aims to review medical tourism and its impact on the United Arab Emirates (UAE) healthcare services. Medical tourism has contributed to the UAE's economy, and the country has mandated international accreditation in public and private facilities to attract patients and boost medical tourism. Accreditation is recognised worldwide as one of the main drivers for implementing quality and patient safety standards, which has sparked considerable interest in studying the effect and impact of this assessment. The second aim of this paper is to review the UAE's strategic goals to improve healthcare services using international accreditation to boost its medical tourism. Although striving to achieve global accreditation attracts tourists, it is essential to the needs and impact of such assessments. The review showed how the UAE healthcare sector has evolved to improve the quality of healthcare services through accreditation. While the development of the health medical industry in the UAE provided many opportunities for expatriates to move to the UAE, the country should aim to strengthen its medical services by expanding to other Middle Eastern countries. This paper could influence policymakers implementing international accreditation in the UAE and the Middle Eastern region.